2017
DOI: 10.4168/aair.2017.9.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Distress and Allergic Diseases in Offspring: Review of Evidence and Possible Pathways

Abstract: Recent studies have suggested a close association between prenatal maternal distress and allergic diseases in the offspring. We selected relevant birth-cohort or national registry studies using a keyword search of the PubMed database and summarized current evidence on the impact of prenatal maternal distress on the development of offspring's allergic diseases. Moreover, we postulated possible pathways linking prenatal distress and allergic diseases based on relevant human and animal studies. Both dysregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Interestingly, some studies have indicated that maternal stress during pregnancy may play a significant role in the development of AD in offspring. It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18–20 years . Possible psycho‐immunological pathways are changes in cytokine levels or oxidative stress transferred by the placenta .…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some studies have indicated that maternal stress during pregnancy may play a significant role in the development of AD in offspring. It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18–20 years . Possible psycho‐immunological pathways are changes in cytokine levels or oxidative stress transferred by the placenta .…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
“…It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18-20 years. [27][28][29][30][31][32][33][34] Possible psycho-immunological pathways are changes in cytokine levels 21 or oxidative stress transferred by the placenta. 35 Psychosocial job strain in general and alcohol intake during pregnancy in particular 36,37 are significant risk factors for AD development in offspring, with alcohol intake being the most prominent risk factor.…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
“…Excessive oxidative stress exposure during human pregnancy has been associated with spontaneous abortion, IUGR, preterm delivery and allergic diseases in the offspring. 147,[196][197][198][199] Evidence, especially in humans, for the involvement of serotonin and tryptophan in the maternalfetal stress transfer is limited. Animal studies, however, provide preliminary evidence of a potential role for serotonin and tryptophan in fetal programming.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…The existing evidence supports that a fraction of the maternal glucocorticoids cross the placenta, deregulates the hypothalamic–pituitary–adrenocortical (HPA) axis of the fetus, and augments the fetal glucocorticoid production ( 41 ). In turn, elevated glucocorticoids of the fetus may lead to a predominance of Th-2 response ( 44 ). It is also known that epigenetic pathways contribute to the regulation of immune development ( 45 ).…”
Section: Prenatal Maternal Stress and Immune Response—airway Inflammamentioning
confidence: 99%